GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 10598823 species occurrences available in GBIF matching the query: Country: Australia BasisOfRecord: Specimen. The dataset includes 10598823 records from 745 constituent datasets: 14866 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 11 records from Scorpaena bulacephala, a new species of scorpionfish (Scorpaeniformes: Scorpaenidae) from the northern Tasman Sea.. 580 records from Naturalis Biodiversity Center (NL) - Crustacea. 3 records from DMNH Eggs. 9 records from Phthiraptera. 1086 records from The molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 95 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 13 records from SPFw - Xiloteca do Instituto de Biociências da Universidade de São Paulo. 7 records from Naturalis Biodiversity Center (NL) - Hymenoptera. 219 records from SUI Vertebrate Collection. 6 records from A revision of the Indo-Pacific fish genus Caragobius (Gobiidae: Amblyopinae).. 6 records from University of Calgary Herbarium. 22130 records from OEH Atlas of NSW Wildlife. 8 records from Dendrogramma, New Genus, with Two New Non- Bilaterian Species from the Marine Bathyal of Southeastern Australia (Animalia, Metazoa incertae sedis) – with Similarities to Some Medusoids from the. 1 records from ISM Mammalogy Collection. 3520 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 1 records from HUEM - Herbário da Universidade Estadual de Maringá. 3 records from CSUC Vertebrate Collection. 9835 records from Phanerogamic Botanical Collections (S). 298 records from Mollusca collection of National Museum of Nature and Science. 1247 records from MVZ Herp Collection (Arctos). 246 records from University of Vienna, Institute for Botany - Herbarium WU. 5 records from uconn-mammals. 4 records from LSUM Bernard Lowy Mycological Herbarium at Louisiana State University - Fungi. 270 records from Herpetile collection, Natural History Museum, University of Oslo. 2294 records from MVZ Mammal Collection (Arctos). 9 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Coelenterata. 95931 records from Australian National Wildlife Collection provider for OZCAM. 5 records from Coleção de Aves do Museu Nacional / UFRJ. 1765 records from LACM Entomology Collection. 5 records from Osteology and phylogeny of Parioglossus (Teleostei, Gobioidei), with a revised key to the species.. 13 records from Orthopteroidea. 1 records from GRBGT: Southern Cape Herbarium Specimen Collections (1882-2008). 3 records from IAC - Herbário do Instituto Agronômico de Campinas. 367 records from QLD DERM Coastal Bird Atlas (Trial). 1247 records from Bee Biology and Systematics Laboratory. 3 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 48 records from Collection of Heteroptera. 1672 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 244 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Aves. 109660 records from AntWeb. 3 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 43 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Types. 5212 records from CAS Entomology (ENT). 648 records from Zoology (Museum of Evolution - Uppsala). 1 records from Lissotes working-group. 106358 records from Naturalis Biodiversity Center (NL) - Botany. 15 records from BOTUw - Xiloteca "Profa. Dra. Maria Aparecida Mourão Brasil". 6 records from Entomological collection of the National Museum. 4 records from CHAS Ornithology. 2 records from TCWC Marine Invertebrates. 228 records from KUBI Ornithology Tissue Collection. 4 records from SPSF - Herbário Dom Bento José Pickel. 1391 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 3418 records from PRECIS. 25889 records from CSIRO Ichthyology provider for OZCAM. 5963 records from Fishbase. 317 records from Occurrence records of southern African aquatic biodiversity. 49 records from The Orthoptera collection (EO) of the Muséum national d'Histoire naturelle (MNHN - Paris). 5 records from SPF - Herbário da Universidade de São Paulo. 130 records from SANT herbarium vascular plants collection. 557 records from The Herpetology Collection at the Staatliches Museum für Naturkunde Stuttgart. 171 records from KUBI Mammalogy Collection. 12 records from Biological Reference Collections ICM CSIC. 1 records from UFP - Herbário UFP - Geraldo Mariz. 1 records from Perot Museum of Nature and Science. 12 records from Six new, unusually small ants of the genus Leptomyrmex (Hymenoptera: Formicidae).. 1067 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 11 records from ICN - Herbário do Instituto de Ciências Naturais. 262 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 1095 records from Lund Museum of Zoology - Insect collections (MZLU). 109 records from URM - Herbário Pe. Camille Torrand. 264 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 4 records from A third species in the rare Australian ant genus Peronomyrmex Viehmeyer (Hymenoptera: Formicidae).. 11381 records from Lyman Entomological Museum (LEMQ). 4 records from Hymenoptera specimen database of Kyushu University. 152870 records from SA Flora (BDBSA). 1 records from NCSM Fishes Collection. 918 records from Western Australia Museum, Crustacea Specimens, Ningaloo Reef - Northwest Cape, Northwest Australia, 1920-2004. 1 records from UAFMC Birds. 5 records from AM: Freshwater Invertebrates (1900-2005). 22 records from The Hymenoptera collection (EY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 6 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 2 records from The Scorpiones collection (RS) of the Muséum national d'Histoire naturelle (MNHN - Paris). 761 records from DMNS Bird Collection (Arctos). 33 records from The Fish Collection at the Zoologische Staatssammlung München. 23 records from ISM Ornithology Collection. 1 records from GENT Lactarius Deliciosi. 1 records from Collection of Hymenoptera. 3 records from Coleção de Echinodermata do Museu Nacional - MNRJ-ECHINO. 28 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 2 records from CESJ - Herbário Leopoldo Krieger. 23 records from The Lepidoptera collection (EL) of the Muséum national d'Histoire naturelle (MNHN - Paris). 843 records from Colección Nacional de Aracnología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 46 records from CUMV Mammal Collection (Arctos). 118 records from CUMV Fish Collection (Arctos). 3162 records from Field Museum of Natural History (Zoology) Bird Collection. 4 records from UAM Mammal Collection (Arctos). 9 records from IZIKO: Marine Invertebrate Collection (1900-2011). 1 records from HSU Wildlife Eggs and Nests. 608 records from The mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from Colección de Algas del Herbario Nacional, Museo Nacional de Historia Natural de Chile. 1035873 records from Museum Victoria provider for OZCAM. 9 records from Eggs Specimen. 393 records from UAM Herbarium (ALA), Cryptogam Collection (Arctos). 25 records from Lioscorpius trifasciatus, a new scorpionfish (Scorpaeniformes: Setarchidae) from the South-West Pacific Ocean.. 11 records from CRCM Vertebrate Collection. 52 records from Cowan Tetrapod Collection - Mammals. 803 records from Herbario Nacional de Plantas Celulares - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 1053 records from MBM - Herbário do Museu Botânico Municipal. 3 records from Colección de Aves de Colombia del Instituto Alexander von Humboldt. 3 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 9 records from Revision of the generic classification of the hawkfishes (Cirrhitidae), with descriptions of three new genera.. 16 records from Gothenburg Herbarium - Types (GBIF:IH:GB:Herbarium). 21241 records from SA Fauna (BDBSA). 696 records from Algae (S). 787 records from Araneae Collection. 1 records from HSU Wildlife Mammals. 40 records from OHN. 1805 records from Field Museum of Natural History (Zoology) Mammal Collection. 1 records from Ichthyologie ZMK. 4 records from MVZ Hildebrand Collection (Arctos). 10 records from Ornithologie ZMK. 348 records from Lund Museum of Zoology (MZLU). 1125 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Pectinoidea. 618 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 5 records from Reptilia ZMK. 11 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 3 records from Crustacea ZMK. 21 records from Mammalogie ZMK. 1546 records from CAS Invertebrate Zoology (IZ). 82 records from Crustacea collection of National Museum of Nature and Science. 620 records from Tallinn Botanic Garden. 21 records from Colección Nacional de Foraminíferos - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 1942 records from Western Australia Museum, Marine Invertebrate Specimens, Ningaloo Reef - Northwest Cape, Northwest Australia, 1952-2004. 1 records from Colección de Zoología Invertebrados - Otros invertebrados. 1 records from UCM Bird Eggs/Nests Collection (Arctos). 1 records from Pseudolycoriella skusei sp. nov. (Diptera: Sciaridae), a new dark-winged fungus gnat from Norfolk Island and Australia. 85 records from UAM Bird Collection (Arctos). 2 records from Herbario MAIA, colección de Eucaliptus del INIA-CIFOR. 27 records from MPM Herpetology. 58 records from A revision the Australian species of the ant genus Myrmecina (Hymenoptera: Formicidae).. 3 records from ISM Herpetology Collection. 22 records from arim. 122 records from Naturalis Biodiversity Center (NL) - Mammalia. 48018 records from Museum of Comparative Zoology, Harvard University. 2 records from Naturalis National Natural History Museum (NL) – Coelenterata. 671 records from Naturalis Biodiversity Center (NL) - Cnidaria. 4899860 records from Australia's Virtual Herbarium. 1 records from Lepidium campestre In Häfliger & Wolf, Documenta Ciba Geigy, Dicot Weeds 1, p. 179. 3 records from Herbier de Strasbourg. 2 records from Kathryn Kalmbach Herbarium. 1 records from NMMNH Mammal. 3316 records from Ichthyology Collection - Royal Ontario Museum. 3982 records from University of British Columbia Herbarium (UBC) - Bryophytes Collection. 220 records from CAS Ornithology (ORN). 3 records from New species of myrmicine ants from Western Australia (Hymenoptera: Formicidae).. 47984 records from Tasmanian Museum and Art Gallery provider for OZCAM. 35 records from Colección Nacional de Mastozoología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 72 records from A new handfish, Brachionichthys australis sp. nov. (Lophiiformes: Brachionichthyidae), with a redescription of the critically endangered spotted handfish, B. hirsutus (Lacepede).. 1 records from Ohio State University Tetrapod Division - Reptile Collection (OSUM). 28 records from New species of ant-mimicking jumping spiders of the genus Myrmarachne MacLeay, 1839 (Araneae: Salticidae) from north Queensland, Australia. 2229 records from CONN. 19 records from HUCS - Herbário da Universidade de Caxias do Sul. 8 records from Type Collection of the Seto Marine Biological Laboratory, Kyoto University. 17 records from NYSM Birds. 18 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 9 records from Cnidaria Collection of the Seto Marine Biological Laboratory, Kyoto University. 227 records from Recent Invertebrates Specimens. 23 records from Hemipteran specimens of Iwate Prefectural Museum. 33 records from Mollusca Collection of Natural History Museum and Institute, Chiba. 386 records from Birds collection of Yamashina Institute for Ornithology. 1 records from Colección de Ofidios Museo de La Salle Bogotá (MLS). 1 records from Coleção de Polychaeta do Museu Nacional. 6 records from Flora of Japan Specimen Database. 10 records from Colección Nacional de Paleopalinología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 1 records from University of Lethbridge Herbarium (LEA). 3641 records from Invertebrates Collection of the Swedish Museum of Natural History. 98 records from KUBI Ichthyology Tissue Collection. 4952 records from Estonian Museum of Natural History. 1351 records from University of California Museum of Paleontology. 120 records from Mammals housed at MHNG, Geneva. 1279 records from DMNS Marine Invertebrate Collection (Arctos). 7 records from ALCB - Herbário Alexandre Leal Costa. 64 records from mel. 307 records from Estonian University of Life Sciences. 2260 records from Essig Museum of Entomology. 1659 records from CAS Ichthyology (ICH). 1052 records from The Diptera collection (ED) of the Muséum national d'Histoire naturelle (MNHN - Paris). 53537 records from NMNH occurrence DwC-A. 508 records from Naturalis National Natural History Museum (NL) – Aves_ Passeriformes. 27 records from The Diatom Collection of Franz Josef Weinzierl at the Botanische Staatssammlung München. 22 records from ARC-PPRI: National Collection Of Fungi(1817-2009). 57 records from DMNS Mammal Collection (Arctos). 1 records from Angelo State Natural History Collections (ASNHC) - Ornithology Collection. 447 records from Mammal collection, Natural History Museum, University of Oslo. 26 records from The Araneae collection (AR) of the Muséum national d'Histoire naturelle (MNHN - Paris). 210 records from Colección Nacional de Invertebrados - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 26 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 281 records from University of British Columbia Herbarium (UBC) - Lichen Collection. 2207 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 25 records from Herbarium specimens of Société des Sciences Naturelles et Mathématiques de Cherbourg (CHE). 55 records from NRM-Herpetology. 1 records from A revision of Malagasy species of Anochetus Mayr and Odontomachus Latreille (Hymenoptera: Formicidae).. 195 records from Bryophyte herbarium, Trondheim (TRH). 13905 records from Illinois Natural History Survey Insect Collection. 1598 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 91 records from Revision of the ant genus Mayriella.. 2 records from Naturalis Biodiversity Center (NL) - Diptera. 31 records from Institut Botanic de Barcelona (IBB-CSIC-ICUB), BC-Lichen. 112 records from Redescription and generic placement of the spider Cryptachaea gigantipes (Keyserling, 1890) (Araneae: Theridiidae) and notes on related synanthropic species in Australasia. 230 records from Herbario Nacional de Plantas Vasculares - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 2 records from Erik Acharius lichen collection. 57 records from CAS Mammalogy (MAM). 6 records from A new genus and five new species of Astieae (Araneae: Salticidae) from Australia, with remarks on distribution. 50 records from UMMZ Mammal Collection. 94 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Coleoptera_Types_Orient. 3 records from R-Criptogamos - Herbário do Museu Nacional - Criptogamos. 1 records from Royal Ontario Museum - Entomology (ROME). 1 records from Herpetology Collection. 2433 records from UMZC Zoological Specimens. 7286 records from AMNH Herpetology Collections. 53 records from Museu de Ciències Naturals de Barcelona: MCNB-Malac. 16 records from Museu de Ciències Naturals de Barcelona: MCNB-Cord. 6 records from Museu de Ciències Naturals de Barcelona: MCNB-ZG. 134 records from Mollusca specimens of Toyama Science Museum. 134 records from Bird Specimens in the Museum of Nature and Human Activities, Hyogo, Japan. 5 records from Invertebrate specimens in the Wakayama Prefectural Museum of Natural History, Japan.. 9 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 1 records from Tissues Specimens. 1815 records from RMT Trawl catch from the 1992/93 V6 KROCK voyage. 6 records from Marine Invertebrata specimen database of Osaka Museum of Natutal History. 15 records from ZFMK DORSA. 34 records from Urolophus kapalensis sp. nov., a new stingaree (Myliobatiformes: Urolophidae) off eastern Australia.. 52 records from Baillon Collection. 347 records from SPF-Algae - Herbário da Universidade de São Paulo - Coleção de Algas. 204 records from SBMNH Vertebrate Zoology. 19 records from Bolus Herbarium Specimens Collection (1865-2009). 168 records from CM Herps Collection. 6 records from UEC - Herbário da Universidade Estadual de Campinas. 2 records from A review of the genus Mystrium (Hymenoptera: Formicidae) in the Indo-Australian region.. 1 records from UWBM Herpetology Collection (Arctos). 3 records from FUEL - Herbário da Universidade Estadual de Londrina. 2 records from Ohio State University Tetrapod Division - Mammal Collection (OSUM). 2034 records from Lepidoptera specimen database of Japan. 2 records from MSB Parasite Collection (Arctos). 6237 records from Field Museum of Natural History (Zoology) Insect, Arachnid and Myriapod Collection. 196375 records from Northern Territory Museum and Art Gallery provider for OZCAM. 527 records from Lichen herbarium, Oslo (O). 2 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 7703 records from LACM Vertebrate Collection. 19 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 32 records from Natural History Museum Rotterdam (NL) - Chordata collection. 10 records from Museu de Ciències Naturals de Barcelona: MCNB-Art. 2 records from Coleopteran specimens of Iwate Prefectural Museum. 5 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 75 records from Marine Invertebrata specimens deposited in the Fukui City Natural History MUSEUM, Japan.. 10 records from Colección Alberto Tinaut (Formicidae). 69 records from Collection Crustacea ZMG. 30 records from Insecta ZMK. 4 records from Akita Prefectural Museum:Hiroki Watanabe Collection of mollusca. 4 records from Insect Collection of Yokosuka City Museum. 64 records from Fossil (WSHN-FO). 137 records from Herbaria of the University and ETH Zürich. 2 records from TRTE Herbarium (TRTE). 347 records from IZIKO South Africa Museum Hymenoptera Collection (1800-2013). 70 records from Revisions of Australian ground-hunting spiders. V. A new lycosoid genus from eastern Australia (Araneae: Tengellidae). 62 records from National Botanic Garden Belgium - Myxomycetes. 1 records from Collection Bryozoa - ZIM Hamburg. 59 records from Collection Crustacea - ZIM Hamburg. 68 records from Collection Oligochaeta - ZIM Hamburg. 138 records from Collection Polychaeta - ZIM Hamburg. 1 records from Collection Tunicata - ZIM Hamburg. 7 records from Collection Bryozoa - ZMB. 27 records from Collection Cnidaria - ZMB. 231 records from Collection Crustacea - ZMB. 53 records from Collection Echinodermata - ZMB. 8 records from Collection Hydrozoa - ZMB. 99 records from Collection Porifera - ZMB. 559 records from Collection Vermes - ZMB. 22 records from Collection Ornithologie - ZSRO. 2 records from Collection Polychaeta - ZSRO. 190 records from The Fungal Collection at the Botanische Staatssammlung München. 4 records from Bush Blitz aids description of three new species and a new genus of Australian beeflies (Diptera: Bombyliidae: Exoprosopini). 556 records from The Vascular Plant Collection at the Botanische Staatssammlung München. 1 records from The Vascular Plant Collection at the Herbarium MSB, Universität München. 1 records from The Mammalia Collection at the Staatssammlung für Anthropologie und Paläoanatomie München. 25 records from The Paleontological Collections at the Bayerische Staatssammlung für Paläontologie und Geologie. 2033 records from The Lichen Collection at the Botanische Staatssammlung München. 46 records from The Exsiccatal Series "Triebel, Microfungi exsiccati". 752 records from The Fungal and Lichen Collections at the Herbarium Marburgense. 9160 records from Tropicos Specimen Data. 3863 records from Natural History Museum Rotterdam (NL) - Mollusca collection. 233 records from SMNK Mantid Collection. 466983 records from Western Australian Museum provider for OZCAM. 1 records from Lepidoptera - SNSD. 849 records from SysTax - Zoological Collections. 102 records from Review of the ant genus Aenictus (Hymenoptera: Formicidae) in Australia with notes on A. ceylonicus (Mayr).. 1 records from Naturhistorisches Museum Mainz, Botanical Collection. 24 records from Naturhistorisches Museum Mainz, Zoological Collection. 1 records from Botanical Research Intitute of Texas. 83699 records from Natural History Museum (London) Collection Specimens. 8 records from Mycology Herbarium, Trondheim (TRH). 2 records from Myriapoda - SMF. 17 records from Botanical Museum, Copenhagen, the Phycology Herbarium. 2304 records from Natural History Museum, Vienna - Herbarium W. 337 records from Phytoplankton samples - 2001/02 V3 CLIVAR. 195 records from Phytoplankton samples - 2001/02 V7 LOSS. 234 records from Phytoplankton samples - 2006/07 V3 SAZ-Sense. 3 records from Plathelminthes - SMF. 125 records from LSUMZ Herp Tissues. 465 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 4 records from Mollusk Collection of Yokosuka City Museum. 155 records from Ichthyology, Kagoshima University Museum. 91 records from Molluscus specimens of Toyohashi Museum of Natural History. 12 records from Harold W. Manter Laboratory of Parasitology Collection. 13 records from Ibaraki Nature Museum, Arthropoda collection. 2 records from Ibaraki Nature Museum, Mammals collection. 1 records from Ibaraki Nature Museum, Fish collection. 2 records from Ibaraki Nature Museum, Birds collection. 184 records from Shellfish specimens in the NISHINOMIYA SHELL MUSEUM, Japan.. 8176 records from RBINS collections. 1 records from Ohio State University Fish Division (OSUM). 2 records from Naturkundemuseum im Ottoneum Kassel, Entomological Collection. 11 records from Field Museum of Natural History (Botany) Fungi Collection. 3 records from The Fungal Collection of Helga Große-Brauckmann at the Botanische Staatssammlung München. 2 records from Collection Hemiptera - SNSD. 2 records from Collection Arachnida - SNSD. 17 records from Collection Trichoptera - SMF. 122 records from Collection Herpetologie - SNSD. 471 records from Herbarium Senckenbergianum (FR) - Fungi. 2 records from Collection Ornithologie - SNSD. 56 records from Collection Malakologie - SNSD. 10 records from Collection Ichthyologie - SNSD. 52 records from Collection Crustacea - SNSD. 15 records from Collection Soil Aninmals. 5 records from Collection Anatomie Histologie - SMF. 3 records from Corvids Literature Database. 131 records from Edaphobase. 98 records from Swiss Psyllid (Hemiptera) Collections - Geneva. 23 records from Swiss Psyllid (Hemiptera) Collections - Basel. 184 records from Parasitic Platyhelminthes Collections. 1 records from Collection Lepidoptera SMF. 631690 records from Australian National Herbarium (CANB). 299 records from ANTARCTIC PLANT DATABASE. 6938 records from Australian Antarctic Division Herbarium. 1183 records from Southern Ocean Continuous Zooplankton Recorder (SO-CPR) Survey. 54 records from Canadian Museum of Nature Herbarium. 77 records from UWBM Mammalogy Collection. 1274 records from UWBM Ornithology Collection. 6 records from Vascular Plant Collection - University of Washington Herbarium (WTU). 180 records from UWFC Ichthyology Collection. 2073 records from CABI Bioscience Fungus Collection. 13 records from UF Florida Museum of Natural History Mammals. 80 records from Fairchild Tropical Botanic Garden Virtual Herbarium Darwin Core format. 15 records from EASIANET. 14 records from The AAU Herbarium Database. 29 records from Real Jardin Botanico, Madrid: MA-Algae. 603 records from Real Jardin Botanico, Madrid: MA-Musci. 1 records from Real Jardin Botanico, Madrid: MA-Hepat. 3 records from Real Jardin Botanico, Madrid: MA-Lichen. 4 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 3733 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 414 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF-Lich. 1 records from NYSM Mammals. 69 records from Herps Specimens. 1 records from Herbario EMMA. Herbario de la Escuela Técnica Superior de Ingenieros de Montes. UPM. 6 records from Museo Nacional de Ciencias Naturales, Madrid: Invertebrados Poliquetos. 118 records from Herbario de la Universidad de Sevilla. 67 records from Herbario de la Universidad de Sevilla, SEV-Historico. 10 records from Museo Nacional de Ciencias Naturales, Madrid. Colección de Tejidos y ADN. 17 records from Institut Botanic de Barcelona, BC. 116 records from Museo Nacional de Ciencias Naturales, Colección de Malacología. 14 records from SeamountsOnline (seamount biota) (CoML). 4 records from Atlantic Reference Centre (OBIS Canada). 1914 records from AIMS - Bioresources Library (OBIS Australia). 102 records from Polycystine Radiolarians from the water column and the surface sediments of the World Ocean (OBIS South America, SOUTHERN OCEAN SUB-NODE). 191 records from Naturalis Biodiversity Center (NL) - Coleoptera. 50 records from DAO Herbarium Type Specimens. 110 records from LSUMZ Herps Collection. 1402 records from Michigan State University Herbarium Lichens. 117 records from BYU Herpetology Collection. 142 records from MSUM Ichthyology and Herpetology Collections. 6 records from LSUMZ Mammals Collection. 164 records from herbario. 267 records from LSUMZ Birds Collection. 20 records from Fish Collection of Yokosuka City Museum. 94 records from Fish Collection of Hokkaido University. 272 records from Lichen Collection of National Museum of Nature and Science. 115 records from Algae Collection of National Museum of Nature and Science. 67 records from Kashihara City Museum of Insect. 48 records from Osaka Prefectural Minoh Park Insects Museum. 266 records from Fish collection of National Museum of Nature and Science. 1 records from Bird collection of National Museum of Nature and Science. 4401 records from C.A. Triplehorn Insect Collection (OSUC), Ohio State University. 13 records from Birds Specimens. 24 records from SDNHM Birds Collection. 37 records from SDNHM Herpetology Collection. 9 records from Fish specimens. 16 records from Arizona State University Amphibian and Reptile Collection. 4217 records from Arizona State University Lichen Collection. 85 records from Arizona State University Vascular Plant Herbarium. 52 records from Galathea II, Danish Deep Sea Expedition 1950-52. 8 records from Botanical Museum, Copenhagen, Mycology Herbarium. 332 records from The Fish Collection. 621 records from The University of Hong Kong Herbarium. 80 records from DAV UC Davis Center for Plant Diversity. 19 records from Database Schema for UC Davis Wildlife museum. 517 records from Bohart Museum of Entomology, UCD. 162 records from Lepidoptera collection of Hannu Saarenmaa. 411 records from University of Alberta Museum of Zoology Ichthyology Collection (UAMZ). 8 records from University of Alberta Museum of Zoology Ornithology Collection (UAMZ). 8 records from Herbarium (UNA). 1 records from CNHE/Coleccion Nacional de Helmintos. 11 records from UNSM Vertebrate Specimens. 29 records from TNHC Herpetology Collection. 6 records from Mammal specimens. 13 records from Mammal specimens. 99 records from MMNH Museum Bird Collection. 20 records from Herp specimens. 2762 records from Vertebrate Zoology Division - Ornithology, Yale Peabody Museum. 346 records from Invertebrate Zoology Division, Yale Peabody Museum. 109 records from Vertebrate Zoology Division - Mammalogy, Yale Peabody Museum. 4 records from TTU Mammals Collection. 114 records from Algaterra Types. 1 records from Bridel Herbar. 2 records from Desmidiaceae Engels. 2088 records from Herbarium Berolinense. 6792 records from Lichen Herbarium Berlin. 788 records from Staatliches Museum für Naturkunde Stuttgart, Herbarium. 113 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 3 records from The Erysiphales Collection at the Botanische Staatssammlung München. 2 records from The Erysiphales Collection at the University Halle-Wittenberg. 44 records from The Myxomycetes Collections at the Botanische Staatssammlung München - Collection of Hermann Neubert. 1 records from The Myxomycetes Collections at the Botanische Staatssammlung München - Collection of Martin Schnittler. 1 records from The Myxomycetes Collections at the Botanische Staatssammlung München - Main Collection. 2306 records from Planetary Biodiversity Inventory Eumycetozoan Databank. 16462 records from invertebratezoology. 71 records from The Collection of Fungi of the Real Jardín Botánico of Madrid (MA-Fungi). 1 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-HEPATICAE. 6 records from Institut Botanic de Barcelona, BC-Histórico. 19 records from Fish Collection of Natural History Museum and Institute, Chiba. 1 records from Visual Plants (144.41.33.158) - Private collection of Rainer Bussmann. 11 records from Visual Plants (144.41.33.158) - Private collection of Juergen Homeier. 4 records from Estacion Biologica Donana - CSIC, Mammal Collection. 1 records from Rust fungus specimen of Research Group of Plant Parasitic Fungi, Biosphere Resource Science and Technology, Graduate School of Life and Environmental Sciences, University of Tsukuba. 99 records from Fish Collection of Kanagawa Prefectural Museum of Natural History. 14 records from Sea shell specimens database of Mr. Toru Ueda collection, Shizuoka Prefecture Museum of Natural History. 238 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 2268 records from Harvard University Herbaria. 14 records from UCLA Donald R. Dickey Bird and Mammal Collection. 3526 records from ORN. 90 records from Herpetology. 11895 records from EURISCO, The European Genetic Resources Search Catalogue. 22 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 2 records from Insect specimens of Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 4 records from Marine invertabrate(ARTHROPODA) specimen database of Osaka Museum of Natural History. 4 records from Marine invertabrate(ECHINODERMATA) specimen database of Osaka Museum of Natural History. 540 records from Marine invertabrate(Mollusca) specimen database of Osaka Museum of Natural History. 1364 records from Plant specimens depodited in Osaka Museum of Natural History, Japan.. 85 records from Itami City Museum of Insects. 2 records from Bird specimens in Gifu Prefectural Museum. 3025 records from Herp Collection. 13545 records from MAL. 37 records from DNA and Tissue Bank of the Natural History Museum of Denmark. 17 records from WNMU Mammal Collection (Arctos). 3616 records from Naturalis Biodiversity Center (NL) - Aves. 6 records from University of Alberta Museum of Zoology Mammalogy Collection (UAMZ). 252 records from University of Alberta Museum of Zoology Amphibian and Reptile Collection (UAMZ). 3 records from UCM Mammal Collection (Arctos). 246 records from Rotifers of Macquarie Island. 15175 records from Mosquito Occurrence Dataset. 414 records from Christopher Walker collection of Glomeromycotan fungi. 8 records from UCM Bird Collection (Arctos). 41 records from UCM Amphibian and Reptile Collection (Arctos). 4 records from Bohart Museum of Entomology, UCD. 154 records from University of Alberta E. H. Strickland Entomological Museum (UASM). 63 records from LSUMZ (LSU MNS) Fishes Collection. 1 records from DIPOL. 3183 records from Field Museum of Natural History (Botany) Bryophyte Collection. 1 records from DIPOL. 1458 records from WFVZ Bird Collections. 13 records from USF Herbarium. 238 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 31 records from UTA Herpetology. 4453 records from UMMZ Herpetology Collection. 6 records from Review of the Camponotus aureopilus species-group (Hymenoptera, Formicidae), including a second Camponotus with a metapleural gland.. 369 records from DORSA - German Orthoptera Collections. 37 records from PSM Vertebrates Collection. 1 records from Herbarium of Namur. 8 records from KUBI Ichthyology Collection. 1201 records from Natural History Museum, University of Tartu. 196 records from Naturalis National Natural History Museum (NL) – Crustacea_Decapoda. 2934 records from University of British Columbia Herbarium (UBC) - Algae Collection. 10 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Pisces_Types. 3 records from MLZ Bird Collection (Arctos). 87 records from Herbarium of Umeå University (UME). 1827 records from Mosses (S). 137 records from Field Museum of Natural History (Botany) Seed Plant Collection. 1 records from MBML-Herbario - Herbário Mello Leitão. 24 records from Ohio State University Tetrapod Division - Bird Collection (OSUM). 7 records from Colección Nacional de Herpetología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 6 records from BOTU - Herbário Irina Delanova Gemtchújnicov. 79 records from UA Herbarium. 2 records from KUBI Invertebrate Zoology Collection. 4 records from R. L. McGregor Herbarium Lichen Collection. 30 records from R. L. McGregor Herbarium Vascular Plants Collection. 23887 records from Therevid PEET Project. 70 records from Exotic terrestrial flatworms, Macquarie Island. 9 records from Molluscan specimen database of Kanagawa Prefectural Museum of Natural History. 13 records from Crustacean specimen detabase of Kanagawa Prefectural Museum of Natural History. 52 records from Insect specimens database of Shizuoka Prefecture Museum of Natural History. 4874 records from Texas A&M University Insect Collection. 38 records from Tulane University Museum of Natural History. 40 records from UAZ Mammals. 26 records from Sukkulentensammlung Zürich. 79 records from Botany Division, Yale Peabody Museum. 538 records from Entomology Division, Yale Peabody Museum. 70 records from Vertebrate Zoology Division - Ichthyology, Yale Peabody Museum. 16 records from DBL_Life. 190 records from Collection Pisces SMF. 1183 records from Collection Arachnology SMF. 36 records from Collection Porifera SMF. 139 records from Collection Mollusca SMF. 36 records from Collection Polychaeta SMF. 516 records from Collection Aves (spirit preserved) SMF. 180 records from Collection Cnidaria SMF. 278 records from Collection Herpetology SMF. 119 records from Herbarium Senckenbergianum (FR). 258 records from Collection Aves (bird skeletons) SMF. 668 records from Collection Mammalia SMF. 771 records from Collection Aves (bird skins) SMF. 218 records from Collection Crustacea SMF. 6 records from Collection Coleoptera SMF. 40 records from Collection Bryozoa SMF. 68 records from Collection Ostracoda SMF. 157 records from Collection Thysanoptera SMF. 465 records from Fish catch from 1996/97 Voyage 2 WASTE (WOCE Antarctic Southern Transect Expedition). 829 records from Spring Phytoplankton Assemblages in the Southern Ocean Between Australia and Antarctica (CLIVAR-SR3). 658 records from Ohio State Acarology Laboratory (OSAL), Ohio State University. 426 records from UAZ Herpetology Collection. 29 records from UAZ Bird Collection. 37528 records from AMNH Bird Collection. 7567 records from AMNH Mammal Collections. 5 records from Bryophyte Collection - University of Washington Herbarium (WTU). 1278 records from Mycological Collection - University of Washington Herbarium (WTU). 17 records from Lichen Collection - University of Washington Herbarium (WTU). 12 records from Museo Nacional de Ciencias Naturales, Madrid: MNCN_Herpeto. 662 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Conidae. 18 records from University of Ghana - Ghana Herbarium. 5 records from Ophiuroidea collections of the Zoological Institute Russian Academy of Sciences. 73 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Herpetology. 2745 records from Entomological Collections (NHRS), Swedish Museum of Natural History (NRM). 2 records from Herbarium specimens of the Muséum d'Histoire Naturelle of Aix-en-Provence (AIX). 426 records from Herpetology Collection. 26 records from HSU Wildlife Birds. 1 records from University of British Columbia - Spencer Entomological Collection (UBCZ). 226 records from Molecular and morphological characterisation of new species in the trapdoor spider genus Aname (Araneae: Mygalomorphae: Nemesiidae) from the Pilbara bioregion of Western Australia. 497 records from SMNS Herpetologie. 98 records from MVZ Egg and Nest Collection (Arctos). 3 records from Precis Plant Data. 27 records from A review of the species in the Apogon fasciatus group with a description of a new species of cardinalfish from the Indo-West Pacific (Perciformes: Apogonidae).. 4 records from Colección Nacional de Ornitología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 89 records from Mammal Specimens. 1274 records from Bird Specimens. 7 records from The reptiles, amphibians and fishes collection (ZA) in the Comparative Anatomy Collection of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from MAC - Herbário do Instituto do Meio Ambiente do Estado de Alagoas. 6 records from A conspectus of the native and naturalized species of Nephrolepis (Nephrolepidaceae) in the world. 3 records from Australian Formicidae.. 11 records from Formicidae Collection Univesity of Granada. 4 records from Description of two new species of Hetereleotris (Gobiidae) from the south Pacific, with a revised key to species and synonymization of the genus Pascua with Hetereleotris.. 2 records from Revision of the genus Euthalenessa Darboux (Polychaeta: Sigalionidae). 396 records from Naturalis Biodiversity Center (NL) - Porifera. 14 records from UPCB - Herbário do Departamento de Botânica. 1 records from Herbarium specimens, Harmas J.H. Fabre (FABR - Sérignan-du-Comtat) of the Muséum national d'Histoire naturelle (MNHN - Paris). 298 records from Naturalis Biodiversity Center (NL) - Cainozoic Mollusca. 58 records from Cardiocondyla atalanta Forel, 1915, a cryptic sister species of Cardiocondyla nuda (Mayr, 1866) (Hymenoptera: Formicidae).. 600103 records from Queensland Museum provider for OZCAM. 2 records from ARC-PPRI: Collection of Southern African bees (1800-2007). 472 records from CM Birds Collection. 62 records from CUMV Amphibian Collection (Arctos). 4492 records from Lund Botanical Museum (LD). 1076 records from Auckland Museum Land Vertebrates Collection. 14442 records from Snow Entomological Museum Collection. 14 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Diptera_Types. 4 records from The Vascular Plant Collection at the Herbarium Tubingense. 1 records from Avena wild species VIR Herbarium. N.I.Vavilov Institute of Plant Genetic Resources (VIR). 89 records from Spider Mites Collection of Jean Gutierrez. 8 records from UAFMC Mammals. 72 records from Reptile Specimens. 176 records from Ouellet-Robert entomological collection (QMOR). 112 records from The Arthropoda Varia Collection at the Zoologische Staatssammlung München. 1039 records from Field Museum of Natural History (Zoology) Fish Collection. 24 records from Aphidoidea Collection. 11 records from MSB Mammal Collection (Arctos). 28 records from MSB Host Collection (Arctos). 18 records from Redescription of two species of wobbegongs (Chondrichthyes: Orectolobidae) with elevation of Orectolobus halei Whitley 1940 to species level.. 32 records from University of Ghent - Zoology Museum - Nematodencollectie. 10 records from William Nylander lichen collection. 884 records from ARC-PPRI: Chalcidoidea Collection (1900-2010). 62 records from National Botanic Garden Belgium - Myxomycetes. 38 records from Colección de Herbario. 1947 records from Naturalis Biodiversity Center (NL) - Chelicerata and Myriapoda. 14 records from The echinoderm collection (IE) of the Muséum national d'Histoire naturelle (MNHN - Paris). 2 records from R-Tipos - Herbário do Museu Nacional - Tipos. 5 records from The cnidarians collection (IK) of the Muséum national d'Histoire naturelle (MNHN - Paris). 9753 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 766 records from Western Australia Museum, Marine Mollusca Specimens, Ningaloo Reef - Northwest Cape, Northwest Australia, 1953-2002. 254 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 10 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 30 records from Description of a new species of catshark, Atelomycterus marnkalha n. sp. (Carcharhiniformes: Scyliorhinidae) from north-east Australia.. 18 records from Description of a new species of weasel shark, Hemigaleus australiensis n. sp. (Carcharhiniformes: Hemigaleidae) from Australian waters.. 4 records from Cirrhigaleus australis n. sp., a new Mandarin dogfish (Squaliformes: Squalidae) from the south-west Pacific.. 8 records from SJRP-Algae - Herbário de algas de São José do Rio Preto. 8550 records from Bernice P. Bishop Museum. 2 records from A review of the genus Potemnemus Thomson, 1864 (Coleoptera: Cerambycidae) with description of a new species from Papua New Guinea. 36 records from DNSM: Durban Natural Science Museum Insect Collection (1900-2011). 1200 records from CUMV Reptile Collection (Arctos). 333 records from The birds collection (ZO) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 68 records from Cowan Tetrapod Collection - Birds. 1 records from ZFMK Sound Archive. 14 records from UTEP Vertebrates. 1101 records from UMMZ Birds Collection. 174903 records from Australian National Insect Collection. 20825 records from Royal Botanic Garden Edinburgh Herbarium (E). 9 records from The Maugean Skate, Zearaja maugeana sp. nov. (Rajiformes: Rajidae) - a micro-endemic, Gondwanan relict from Tasmanian estuaries.. 7 records from Hymenoptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 16 records from Fundación Miguel Lillo - Colección Herpetológica. 3 records from Colección de Mastozoología. 4 records from Pseudoplesiops wassi, a new species of dottyback fish (Teleostei: Pseudochromidae: Pseudoplesiopinae) from the West Pacific.. 5896 records from Botany (UPS). 90 records from Aves Collection of Institute of Systematics and Evolution of Animals. 365 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Platyhelminthes. 20 records from DMNH Birds. 23 records from Instituto de Ciencias Naturales. 145 records from NRM-Fishes. 174 records from Museu de Ciències Naturals de Barcelona: BGJBB. 159 records from Type herbarium, Göttingen (GOET). 4 records from DMNS Egg Collection (Arctos). 73 records from ARC-PPRI: National Collection Of Fungi(1817-2009). 330 records from Mammalogy Collection - Royal Ontario Museum. 23 records from UNR Herpetology. 1 records from Four new species of deep-water catsharks of the genus Parmaturus (Carcharhiniformes: Scyliorhinidae) from New Caledonia, Indonesia and Australia.. 18 records from MSB Bird Collection (Arctos). 72 records from University of British Columbia Herbarium (UBC) - Fungi Collection. 14 records from EAC - Herbário Prisco Bezerra. 227 records from Amphibians and Reptiles collection at the Natural History Museum of Denmark (SNM). 19 records from Coleção Ictiológica (MNRJ), Museu Nacional (MN), Universidade Federal do Rio de Janeiro(UFRJ). 235 records from Herbarium specimens of Université de Montpellier 2, Institut de Botanique (MPU)). 28 records from ESA - Herbário da Escola Superior de Agricultura Luiz de Queiroz. 894 records from Bryophyte herbarium, Göttingen (GOET). 12 records from R - Herbário do Museu Nacional. 30133 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 1014 records from Herpetology Collection - Royal Ontario Museum. 6797 records from CAS Herpetology (HERP). 6 records from Lethrinus ravus, a new species of emperor fish (Perciformes: Lethrinidae) from the western Pacific and eastern Indian oceans.. 8 records from Arachnida e Myriapoda Museu Nacional (MNRJ ARAC). 2892 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 5 records from Caire-Chabrand Collection. 103 records from Ditsong Museum. 2 records from Ecsenius caeruliventris and E. shirleyae, two new species of blenniid fishes from Indonesia, and new distribution records for other species of Ecsenius.. 26 records from A new tarantula species from northern Australia (Araneae, Theraphosidae). 1 records from A new species of the gobiid fish Trimma from the Western Pacific and Northern Indian Ocean coral reefs, with a description of its osteology.. 7 records from Wilson Botanical Garden - Las Cruces Biological Station. 36 records from NCSM Invertebrates Collection. 481 records from UB - Herbário da Universidade de Brasília. 1 records from Pastinachus solocirostris sp. nov., a new species of Stingray (Elasmobranchii: Myliobatiformes) from the Indo-Malay Archipelago.. 6 records from Acanthopagrus taiwanensis, a new sparid fish (Perciformes), with comparisons to Acanthopagrus berda (Forsskål, 1775) and other nominal species of Acanthopagrus.. 63 records from The Hemiptera collection (EH) of the Muséum national d'Histoire naturelle (MNHN - Paris). 414 records from Green Plant Herbarium (TRT). 12119 records from Naturalis Biodiversity Center (NL) - Mollusca. 1 records from Live birth in the Devonian period. 40 records from The crustaceans collection (IU) of the Muséum national d'Histoire naturelle (MNHN - Paris). 117 records from A review of the ant genus Myrmecorhynchus (Hymenoptera: Formicidae). 59 records from Systematics of the family Ariidae (Ostariophysi, Siluriformes), with a redefinition of the genera.. 2091 records from KUBI Herpetology Collection. 1069001 records from Australian Museum provider for OZCAM. 22 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 1 records from HCF - Herbário da Universidade Tecnológica Federal do Paraná Campus Campo Mourão. 82 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Lichens. 15 records from Gothenburg Herbarium - General (GBIF:IH:GB:Herbarium). 8 records from Synonymy of Homalopoltys (Araneae: Araneidae) with the genus Dolichognatha (Araneae: Tetragnathidae) and descriptions of two new species. 3375 records from Allan Herbarium (CHR). 26 records from NOAA Deep Sea Corals Research and Technology Program. 3 records from Cowan Tetrapod Collection - Herpetology. 104 records from Entomology at ZMUC, Natural History Musem of Denmark. 625 records from The nematodes collection (IN) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from Journal of Natural History. 221 records from Systematics, distribution and biology of the Australian ' micro-flea' wasps, Baeus spp. (Hymenoptera: Scelionidae): parasitoids of spider eggs.. 2 records from CEN - Herbário da Embrapa Recursos Genéticos e Biotecnologia. 2003 records from MVZ Bird Collection (Arctos). 1 records from Colección Nacional de Actuopalinología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 3104 records from Vascular Plant Herbarium, Oslo (O). 6495 records from Field Museum of Natural History (Zoology) Amphibian and Reptile Collection. 4 records from The Bergius Herbarium. 2 records from Mycology herbarium, Oslo (O). 8 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 1561 records from KUBI Ornithology Collection. 138 records from Palaeobiology - Vertebrate Comparative Osteology Collection - Royal Ontario Museum. 1 records from On the Australian linyphiid spider Alaxchelicera ordinaria Butler, 1932 (Araneae). 258 records from Tromsø Museum, Lichens. 1 records from E. C. Smith Herbarium (ACAD). 3 records from UAIC Ichthyological Collection. 19 records from NCSM Mammals Collection. 14 records from Invertebrata Collection of Institute of Systematics and Evolution of Animals. 1 records from A spectacular new species of seadragon (Syngnathidae). 28 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 43 records from UF FLMNH Ichthyology. 1 records from The Pisces Collection at the Staatssammlung für Anthropologie und Paläoanatomie München. 2847 records from New Zealand Fungal and Plant Disease Collection (PDD). 39 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 306 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Porifera. 61 records from The Coleoptera collection (EC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 317 records from Fish collection, Natural History Museum, University of Oslo. 2 records from Diptera. 51 records from SaIticidae (Araneae) of Oriental, Australian and Pacific Regions, IV. Genus Ocrisiona Simon, 1901. 4223 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 162 records from Invertebrates (Type Specimens) of the Swedish Museum of Natural History. 18 records from SP-Bryophyta - Maria Eneyda P. Kauffman Fidalgo. 2 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Bryophytes. 10 records from Fundación Miguel Lillo - Colección Criptogámica. 25 records from Collection Mammalogie - ZSRO. 35 records from SysTax - Herbaria. 3 records from Three new species of Microbrotula (Teleostei: Ophidiiformes: Bythitidae) from the Indo-West Pacific.. 4400 records from Geneva Herbarium – General Collection (G). 1537 records from The fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 184 records from Instituto de Botánica Darwinion. 1535 records from Ornithology Collection Passeriformes - Royal Ontario Museum. 2 records from SJRP - Herbário de São José do Rio Preto. 54 records from Herbarium WRSL, Main Collection. 26 records from CAS Botany (BOT). 494 records from CUMV Bird Collection (Arctos). 5 records from PACA-Fungi - Herbarium Anchieta - Fungi Rickiani. 151267 records from South Australian Museum Australia provider for OZCAM. 427 records from International Fossil Shell Museum (NL) - Mollusca Collection. 378 records from Lichen herbarium, UiB. 155 records from Algae herbarium, Trondheim. 147 records from LSUMZ Bird Tissues. 298 records from Naturalis Biodiversity Center (NL) - Amphibia and Reptilia. 3 records from CHAS Oology Collection (Arctos). 1888 records from Fungi (S). 4 records from PACA-AGP - Herbarium Anchieta. 1596 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 138 records from pins. 334 records from SP-Fungi - Maria Eneyda Pacheco Kauffmann Fidalgo.
Keywords: GBIF; biodiversity; species occurrences